THE AUTHOR(S) OF THE PHD THESIS AND HIS/THEIR MORAL RIGHTS. JOINT LIABILITY OF THE PHD CANDIDATE AND OF THE PHD SUPERVISOR FOR THE OBSERVANCE OF THE ETHICS AND DEONTOLOGY RULES - Ionela-Alina ZORZOANĂ (Challenges of the Knowledge Society)
In the first part, this study proposes an analysis of the phrase “Author(s) of the PhD thesis” by reference to the principle The real author of the PhD thesis and the moral rights of the author of a scientific work provided by Law no. 8/1996 on copyrights and related rights. We thought it was necessary to pay special attention to the right of informing the public about the work, in the light of the limitations provided by law in case of PhD theses, especially by the Law of National Education no. 1/2011, Law no. 288/2004 on organizing PhD academic studies and Government Decision no. 681/2011 for the approval of the Code of PhD academic studies. The analysis mainly refers to the guidance activity carried out by the PhD supervisor throughout the PhD study years, an obligation provided by Law no. 1/2011 and Government Decision no. 681/2011. Thus, in the first part of the study, we shall answer the question whether the guidance activity of the PhD supervisor is sufficient, so that he should become the author of the PhD thesis alongside the PhD candidate and benefit of the moral rights to the same extent as the latter. In the second part of the study, we proposed ourselves to analyze the joint liability of the PhD candidate and of the PhD supervisor for the observance of the rules of ethics and deontology, by relating such to the guidance obligation of the PhD supervisor. We shall perform this analysis by reference to the said regulations, but also to Law no. 206/2004 on the proper conduct in research activity and Law no. 319/2003 on the status of the research-development staff.